Предмет: Алгебра,
автор: kostil0007
упростите выражение, пожалуйста)
Приложения:
![](https://files.topotvet.com/i/7f6/7f6f88ddee733d0ad12757869916ae85.jpg)
Ответы
Автор ответа:
0
(3a³ -81b³)/(18b²a+6a²b+2a³) + (81a²b - 54ab²+9b³)/(2ab² - 12ba² + 18a³ ) = 3(a³ -(3b)³)/2a(9b² +3ab +a²) +9b(9a² -6ab+b²)/2a(b² -6ab +9a²) =
=3(a -3b)(a² +3ab+9b²)/2a(9b² +3ab +a²) +9b/2a = 3(a -3b)/2a +9b/2a =
(3(a-3b) +9b)/2a =(3a-9b +9b)/2a = 3a/2a =1,5.
* * * 9a² -6ab+b² =(3a -b)² ; A³ - B³ =(A -B)(A² +A*B +B²) * * *
=3(a -3b)(a² +3ab+9b²)/2a(9b² +3ab +a²) +9b/2a = 3(a -3b)/2a +9b/2a =
(3(a-3b) +9b)/2a =(3a-9b +9b)/2a = 3a/2a =1,5.
* * * 9a² -6ab+b² =(3a -b)² ; A³ - B³ =(A -B)(A² +A*B +B²) * * *
Похожие вопросы
Предмет: Алгебра,
автор: vasileva197923
Предмет: Алгебра,
автор: czx7129h
Предмет: Геометрия,
автор: thirdfen4
Предмет: Математика,
автор: ilser70